Feeding obese dogs during weight loss is on average cost‐neutral. (12th February 2015) - German, A. J.; Luxmore, J.; Holden, S. L.; Morris, P. J.; Biourge, V.
<x xml:space="preserve">Abstract</x> OBJECTIVES The cost of feeding a purpose‐formulated weight loss diet may deter owners of obese dogs from proceeding with a weight loss programme. The current study aimed to compare average food costs during weight loss with those before weight loss. MATERIALS AND METHODS Average daily food costs, for before and during weight loss, were calculated in 22 obese dogs that had successfully completed weight management. RESULTS The median food cost before weight loss was £0 · 52/day (£0 · 24–3 · 31/day), for main meal only, and £0 · 64/day (£0 · 26–3 · 31/day) for main meal and additional food (table scraps and treats). The median food cost during weight loss was £0 · 90/day (£0 · 26–1 · 36/day), and no additional food was given. The average daily feeding costs during weight loss did not differ from pre‐weight‐loss costs, either with (P = 0 · 425) or without (P = 0 · 222) the additional food included. CLINICAL SIGNIFICANCE Knowledge that average diet costs do not significantly differ from food costs prior to weight loss may help veterinarians to persuade owners to enrol obese dogs in a weight management programme.